Mechanisms involved in the regulation of neuropeptide-mediated neurite outgrowth: a minireview - Lestanova Z. (Sciendo, 2016)
The present knowledge, regarding the neuronal growth and neurite extension, includes neuropeptide action in the central nervous system. Research reports have brought much information about the multiple intracellular signaling pathways of neuropeptides. However, regardless of the differences in the local responses elicited by neuropeptides, there exist certain functional similarities in the effects of neuropeptides, mediated by their receptors. In the present review, data of the relevant studies, focused on G protein-coupled receptors activated by neuropeptides, are summarized. Particularly, receptors that activate phosphatidylinositol-calcium system and protein kinase C pathways, resulting in the reorganization of the neuronal cytoskeleton and changes in the neuronal morphology, are discussed. Based on our data received, we are showing that oxytocin increases the gene expression of GTPase cell division cycle protein 42 (Cdc42), implicated in many aspects of the neuronal growth and morphology. We are also paying a special attention to neurite extension and retraction in the context of neuropeptide regulation.